Strengthening the Regional Innovation Ecosystem as the Foundation for the Development of Jatim Innovation Connect in East Java Province - Prawitra Thalib; Sonny Kristianto; Fitri Dianitasari; Firda Rahmania; Vindha Tyas Restianingati; Andriyanto Andriyanto (Fakultas Syariah IAIN Langsa, 2026)
Ideally, a regional innovation ecosystem should be systemically integrated to encourage downstream research, economic growth, and public welfare. However, in reality, East Java Province faces an innovation paradox, where the high quantity of innovation is not accompanied by connectivity between actors (Triple/Quadruple Helix), resulting in innovation tending to be fragmented, seasonal, and with minimal economic impact. This study aims to analyze the condition of the regional innovation ecosystem and formulate strategies for strengthening it as a foundation for the development of the Jatim Innovation Connect (JIC) platform. The method used is descriptive qualitative, with data collected through in-depth interviews with key informants (BRIDA, academics, industry, and innovators) selected through purposive sampling, field observations, and literature review. The results indicate that the East Java innovation ecosystem is in a phase of active but immature growth (growing but fragmented). Strengthening the ecosystem requires BRIDA as an orchestrator and JIC as a digital innovation intermediary to match research potential (supply) with industry needs (demand). The success of this strategy depends on strengthening regional regulations, sustainable funding schemes, facilitating intellectual property rights (IPR), and establishing a culture of collaboration between actors.